2012
DOI: 10.1002/jmri.23752
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and precision of vessel area assessment: Manual versus automatic lumen delineation based on full‐width at half‐maximum

Abstract: Purpose:To evaluate the accuracy and precision of manual and automatic blood vessel diameter measurements, a quantitative comparison was conducted, using both phantom and clinical 3D magnetic resonance angiography (MRA) data. Since diameters are often manually measured, which likely is influenced by operator dependency, automatic lumen delineation, based on the full‐width at half‐maximum (FWHM), could improve these measurements.Materials and Methods:Manual and automatic diameter assessments were compared, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…For λ > 5 in Figure 1C, the error drops below 5% and by λ ≥ 10, it has fallen below 2% (compared to roughly 5% for the undersized boundary case). This agree with the findings from Merkx et al based on FWHM in uCT [5]. …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For λ > 5 in Figure 1C, the error drops below 5% and by λ ≥ 10, it has fallen below 2% (compared to roughly 5% for the undersized boundary case). This agree with the findings from Merkx et al based on FWHM in uCT [5]. …”
Section: Resultssupporting
confidence: 93%
“…This is especially a problem when working with poor resolution or slow flow rates, such as with cerebral spinal fluid in the aqueduct [4]. Automatic segmentation algorithms generally provide improved consistency and efficiency [5]. Various algorithms for automatic or semi-automatic segmentation based on full width half maximum, thresholding, active contour modeling, and dynamic programming have been proposed [59], yet a thorough comparison of these methods with a theoretical backing is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The FWHM method is often used to detect the vessel boundary, which provides a robust estimation of the lumen's edge and is less sensitive to noise and adjacent structures than other edge criteria. 20 A previous study reported that the precision error was below 3z and the accuracy error below 10z in measuring the vessel diameter with the FWHM method for resolutions above 2 pixels/diameter using contrast-enhanced timingrobust angiography (CENTRA). 20 Another study reported underestimation of vessel diameter up to 20z in measuring using the FWHM method for resolutions between 1.3 and 3 pixels/diameter and time of ‰ight (TOF).…”
Section: Discussionmentioning
confidence: 99%
“…20 A previous study reported that the precision error was below 3z and the accuracy error below 10z in measuring the vessel diameter with the FWHM method for resolutions above 2 pixels/diameter using contrast-enhanced timingrobust angiography (CENTRA). 20 Another study reported underestimation of vessel diameter up to 20z in measuring using the FWHM method for resolutions between 1.3 and 3 pixels/diameter and time of ‰ight (TOF). 21 In the present study, the number of pixels per mean nerve diameter ranged from approximately 2 to 3 pixels/diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other smaller vessels in the body, capillaries have a much smaller diameter (5-10 m), which is barely sufficient for erythrocytes to pass through [10]. The friction between blood cells and the vascular wall will be greater.…”
Section: Resistance To Capillary Bed Blood Flowmentioning
confidence: 99%